1998
DOI: 10.1007/s002940050347
|View full text |Cite
|
Sign up to set email alerts
|

Identification of three ubiquitin genes of the rice blast fungus Magnaporthe grisea , one of which is highly expressed during initial stages of plant colonisation

Abstract: Differential cDNA screening was used to identify genes expressed during the colonisation of rice leaves by the pathogenic fungus Magnaporthe grisea. This led to the identification of a gene, called UEP1, which encodes a ubiquitin extension protein. UEP1 was highly expressed 48 h after initial fungal infection of rice leaves when M. grisea is proliferating in the leaf epidermis but not yet causing disease symptoms. UEP1 appeared to be down-regulated after this time despite further extensive growth of the fungus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 41 publications
3
14
0
Order By: Relevance
“…pombe have been identified (D00926) indicating active protein turnover during early B. graminis germling development. This notion is corroborated by similar observations during initial plant colonization by M. grisea (McCafferty and Talbot, 1998).…”
Section: Discussionsupporting
confidence: 86%
“…pombe have been identified (D00926) indicating active protein turnover during early B. graminis germling development. This notion is corroborated by similar observations during initial plant colonization by M. grisea (McCafferty and Talbot, 1998).…”
Section: Discussionsupporting
confidence: 86%
“…This stress, in turn, could indirectly block differentiation. The ubiquitin/26S proteasome pathway is required for the stress response in many eukaryotes, and stressful conditions, such as growth on amino acid analogs, upregulates the synthesis of ubiquitin and other components of the pathway in yeast, animals, and plants (Finley et al, 1987;Burke et al, 1988;Feussner et al, 1997;Mathew et al, 1998;McCafferty and Talbot, 1998). The observation that the overall levels of free ubiquitin and ubiquitin chains are elevated in the ⌬mcb1 strains is congruent with this stress effect ( Figure 5A).…”
Section: Discussionsupporting
confidence: 71%
“…These studies have shown that an ubiquitin-encoding gene (UEP3) (McCafferty and Talbot, 1998), the gene encoding the mitochondrial small-subunit rRNA (Talbot and Tongue, 1998), and MPG1 encoding a class I hydrophobin, which is one of the most expressed M. grisea genes (Talbot et al, 1993), are strongly expressed during the colonization of the plant by the fungus. Since then, medium to large-scale expressed sequence tag (EST) projects as well as a SAGE analysis have allowed the discovery of novel M. grisea genes expressed during a susceptible infection using RNAs extracted from infected rice leaves (Kim et al, 2001;Rauyaree et al, 2001;Matsumura et al, 2003).…”
Section: Grisea Genes Expressed During Infectionmentioning
confidence: 99%